(untitled) (BIRDEM Medical Journal, 2019)
Background: Cirrhosis of liver is the most common cause of liver disease in our country. It is an important cause of mortality and morbidity. Hepatitis B and Hepatitis C virus infection are the important causes of liver disease in our country. Many people present to us with established cirrhosis of liver. The aim of our study is to compare the demographic and virological profiles between diabetic and non-diabetic patients with cirrhosis of liver. Methods: This cross-sectional study was carried out from July 2018 to December 2018 in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital and in Supreme Medical Services, Jatrabari, Dhaka. Cirrhosis of liver was diagnosed with the help of ultrasonography of whole abdomen, endoscopy of upper gastro-intestinal tract (GIT), fibroscan of liver and liver biopsy where indicated. Results: Total 465 cases were enrolled in this study. Of them 272 patients were diabetic and 193 patients were non- diabetic. The study reached its various findings from the view point in our country. Most diabetic patients were between the age 51 to 60 (57.4%) and in non-diabetic patients between the age 41 to 50 (31.1%) (p<.001). Cirrhosis of liver was more common in non-diabetic, male (69.4%) patients but it was more common in female (48.2%), diabetic patient (p<.001). Female patients were mostly house wife in both diabetic (45.2%) and nondiabetic group (24.9%) (p<.001). Male patients were mostly in service in both diabetic (20.6%) and in nondiabetic group (32.6%) (p<.001). Most of the people live in urban area in both diabetic (70.6%) and nondiabetic group (53.9%) (p<.001). Hepatitis B virus infection was significantly higher in cirrhotic, non-diabetic than diabetic group (49.7% vs 21.3%) (p<0.001) but Hepatitis C virus infection was significantly higher in cirrhotic diabetic group than non-diabetic group (14.3% vs 8.8%) (p<0.001). Conclusion: Hepatitis B virus is the leading cause of cirrhosis of liver in male, non-diabetic patient and Hepatitis C virus is the leading cause of cirrhosis of liver in female, diabetic patient. Birdem Med J 2019; 9(3): 229-233